A remarkable new species of winter stonefly (Plecoptera: Capniidae) from Southeastern China - Du, Yu-Zhou; Chen, Zhi-Teng (Zootaxa, 2016)
A new species of the genus Capnia s.l., C. zijinshana Du & Chen, sp. nov. is described and illustrated from Jiangsu Province, of southeastern China. The new species is distinguished from other known Chinese capniid species by the unique thoracic sclerites and genitalic characters.